Methionine sulfoxide reductase A protects neuronal cells against brief hypoxia/reoxygenation - Yermolaieva, Olena (National Academy of Sciences, 2004)
Hypoxia/reoxygenation induces cellular injury by promoting oxidative stress. Reversible oxidation of methionine in proteins involving the enzyme peptide methionine sulfoxide reductase type A (MSRA) is postulated to serve a general antioxidant role. Therefore, we examined whether overexpression of MSRA protected cells from hypoxia/reoxygenation injury. Brief hypoxia increased the intracellular reactive oxygen species (ROS) level in PC12 cells and promoted apoptotic cell death. Adenovirus-mediated overexpression of MSRA significantly diminished the hypoxia-induced increase in ROS and facilitated cell survival. Measurements of the membrane potentials of intact mitochondria in PC12 cells and of isolated rat liver mitochondria showed that hypoxia induced depolarization of the mitochondrial membrane. The results demonstrate that MSRA plays a protective role against hypoxia/reoxygenation-induced cell injury and suggest the therapeutic potential of MSRA in ischemic heart and brain disease.